Perception of Farmers towards Effectiveness of Extension Services of KVK (Indian Journal of Extension Education, 2020)
The present investigation was carried out to determine the perception of the contact farmers towards extension service extended through Krishi Vigyan Kendra (KVK) working in the Amravati division of Maharashtra state. The total sample comprised 240 contact farmers who were selected by using simple random sampling; and data were gathered by personally interviewing to elicit the requisite information. The results indicated that majority of the contact farmers were in the middle age group, educated up to college to university level, further it was observed that these respondents were engaged in diversified occupations with semi-medium land holding having moderate farming experience, extension contacts with adequate scientific orientation and innovativeness. Perception of the farmers towards the extension service was measured on the basis of three dimensions viz. Knowledge disseminated, Field & diagnostic visits, and Mass media & group discussion utilized by the Subject Matter Specialists for the dissemination of the generated technology towards its end users. The findings indicated that a larger proportion (57.50%) and nearly one third (30.83%) of the respondents perceived that extension service of KVK was ‘useful’ and ‘more useful’ for them, respectively. Further, the relational analysis revealed that extension contact, training received, scientific orientation and innovativeness had positive and highly significant, whereas age, education, and farming experience were established a positive and significant relationship with the perception of farmers towards extension service of KVK.